Silver-based dressings for the prevention of surgical site infections: evidence from randomized trials - S. Younes (22254238) (2025)
Background Surgical site infections (SSIs) are a major cause of postoperative complications, increasing morbidity and healthcare costs. Silver-based dressings are commonly used due to their antimicrobial properties, but their effectiveness in reducing SSIs remains unclear. Aim To evaluate the efficacy of silver-based dressings compared with non-silver dressings in preventing SSIs in randomized controlled trials (RCTs). Methods A systematic search was conducted in PubMed, Cochrane Library and Embase to identify RCTs comparing silver-based dressings with non-silver dressings for the prevention of SSIs. The study protocol was registered in PROSPERO (CRD42024592966). Meta-analysis using a random-effects model calculated pooled risk ratios (RR) with 95% confidence intervals (CI). Heterogeneity was assessed with the I2 statistic, and publication bias was evaluated through funnel plots and Egger's test. Results Twelve RCTs with 2928 participants were included in the meta-analysis. Silver-based dressings reduced the risk of SSIs by 40% compared with non-silver dressings (RR 0.60, 95% CI 0.41–0.89; P<0.05); this difference was significant. Heterogeneity was moderate (I2=53%). Conclusions Silver-based dressings reduce the risk of SSIs significantly; however, further high-quality RCTs are needed to confirm their benefits across different surgical contexts and patient populations. Other Information Published in: Journal of Hospital Infection License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jhin.2025.04.026